Dietary branched-chain amino acids intake and coronary artery calcium progression: insights from the coronary artery risk development in young adults (CARDIA) study. - Hao, Qing-Yun; Weng, Jun; Zeng, Ting-Ting; Zeng, Yu-Hong; Guo, Jing-Bin; Li, Shi-Chao; Chen, Yi-Ran; Yang, Ping-Zhen; Gao, Jing-Wei; Li, Ze-Hua (European Journal of Nutrition, 2025)
Objective: Branched-chain amino acids (BCAA) have been implicated in the risk of cardiovascular disease. However, it is unclear whether dietary BCAA intake, specifically isoleucine, leucine, and valine are associated with coronary artery calcium (CAC) progression. Methods: We included the participants from the Coronary Artery Risk Development in Young Adults (CARDIA) study cohort for the analysis. Dietary intake of BCAA was assessed at year 7 of the study. CAC was measured using standardized computed tomography scans at years 15, 20, and 25. CAC progression was defined as follows: for participants with a baseline CAC of 0, progression was defined as CAC > 0 at follow-up; for those with 0 < baseline CAC < 100, progression was defined as an annualized change of ≥ 10; and for those with baseline CAC ≥ 100, progression was defined as an annualized percent change of ≥ 10%. Multivariate adjusted Cox regression models were utilized to examine the associations between BCAA intake and CAC progression. Results: Among 2381 included participants (average age 40.4 ± 3.5 years, 44.9% men), 629 participants (26.4%) exhibited CAC progression during a follow-up period of 8.90 ± 2.03 years. In the fully adjusted model, high intake of total BCAA, and its individual components, isoleucine, leucine, and valine were associated with an increased risk of CAC progression by 35.6% (HR, 1.356 [95% CI, 1.040–1.769]), 30.5% (HR, 1.305 [95% CI, 1.001–1.701]), 30.9% (HR, 1.309 [95% CI, 1.003–1.706]), and 33.9% (HR, 1.339 [95% CI, 1.026–1.747]), respectively, compared to their corresponding low intake groups. The associations were consistent across various subgroups, including age, sex, race, and body mass index, but were stronger in participants without baseline CAC (interaction P < 0.001). These results remained robust in a series of sensitivity analyses. Conclusions: High dietary intake of BCAA, including isoleucine, leucine, and valine, were independently associated with an increased risk of CAC progression. The findings may implication for dietary modifications in primary prevention of subclinical atherosclerosis. Registration: URL: ; Unique identifier: NCT00005130.Highlights: Branched-chain amino acids (BCAAs), including isoleucine, leucine, and valine, are independently associated with increased risk of coronary artery calcium (CAC) progression. This positive association is stronger in individuals without baseline CAC, but remain robust across various sensitivity analyses. These data suggest that high BCAA intake should be considered cautiously, particularly in the absence of CAC, to avoid potential adverse effects on the development of coronary atherosclerosis.